Should I stay or should I go? Skilled immigrants' perceived brain-waste and social embeddedness - Farivar, F.; Cameron, R.; Dantas, Jaya A R (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose: Drawing on embeddedness theory, we examine how skilled immigrants' perceived brain-waste affects their social embeddedness. Social embeddedness facilitates the acquisition of host country-specific human capital, which, in return, can accelerate the transfer of immigrants' human capital in the workplace.